Active mobility perception from an intersectional perspective: Insights from two European cities - Carboni, A. (2022)
The investigation of active mobility perception for different classes of users is crucial to include all mobility needs and increase the accessibility of these modes. Elements like the perception of safety, security and the shape of the urban environment (e.g., provision of cycle paths) are to be considered while analyzing the different mobility choices between men and women. The current study focuses on the answers of a survey among representative samples of the population of two European cities, namely Valencia and Turin. Data collected in these similarly structured ‘bike friendly’ sites are compared following an intersectional approach based on gender and age. The results showed, for example, that, in general, cyclists are somewhat affected by safety issues, especially in terms of sharing space with motor vehicles. Or that women are less satisfied with the level of safety during walking. When considering bike-sharing, women seem more responsive to adding a dedicated space for children to start using this mode. The analysis of the results helps in providing interesting indications and suggestions for transport planning.